Caracterização de um compósito metal duro/aço rápido para o desenvolvimento de um FGM - Paula, Daniella Gualberto Caldeira de (2022)
Although cemented carbide is a cutting tool widely used in machining, mechanical and thermal cracks may happen owing to lack of fracture toughness. An innovative way to improve the material properties is to use the Functionally Graded Materials (FGM) concept. FGM are composites made of two or more different materials tailored in a gradient form. Cemented carbide and high-speed steel are two important and distinct groups of cutting tool materials. The former is characterized by its high hardness, while the latter by its toughness. Therefore, this work aims to evaluate physical and mechanical properties of cemented carbide/high-speed steel composite with TiC addition and compare them with those of a commercial cemented carbide tool. Next, present a structural design of a cemented carbide/high-speed-steel FGM, considering residual stress. For this, cemented carbide (particle size 1.5 μm), high-speed steel (50 μm) and TiC (0.1 μm) powders were sintered varying the TiC volume fraction from 5 to 35% at 1200ºC, under uniaxial pressure of 20 MPa and 2.2 MPa, using the technique of the technique of pulsed electric current sintering (PECS). The relative density, was determined based on the Archimedes principle. The mechanical properties, hardness and fracture toughness were conducted using a Vickers indenter. The results showed a great influence of the sintering pressure on the relative density and, consequently, on the mechanical properties. For the 5% TiC sample sintered at 20 MPa, the relative density was 97.8%, close to the commercial cemented carbide, 98.1%. Considering mechanical properties, the 5% TiC sample obtained the Vickers hardness number of 1242 ± 62 HV and fracture toughness of 12.5 ± 1.3 MPa.m1/2 , whereas the commercial sample obtained 1284 ± 176 HV and 13.0 ± 1.3 MPa.m1/2. For samples sintered at 2.2 MPa with TiC addition of 15 to 35%, loss of relative density and mechanical properties were observed as the volume fraction of TiC increased. Except for 15% TiC, which attained higher fracture toughness, 13.3±1.0 MPa.m1/2. In this case, the porosity may have absorbed the fracture energy. In addition, from 25% TiC sample the iron segregation amount decreased in the microstructure. The structural design of the FGM considered 5 layers and showed compressive stresses in the first layers rich in carbide content. The results showed the importance of applying pressure during sintering to achieve high relative density and mechanical properties. Furthermore, it is desirable to control the TiC content to have a microstructure more homogenous. The residual stress prediction suggests that the FGM is feasibility without crack.